Women's Empowerment Through Regional Batik Training & Training on Making Promotional Digital Media as a Means of Branding the People of Curuglemo Village - Setiyawan, Clemens Felix (Jurnal Sinergitas PKM & CSR, 2023)
Curuglemo Mandalawangi Pandeglang Banten Village has village potential including natural tourism, agricultural products and local wisdom culture. Curuglemo Village will develop tourism based on agriculture and plantations, arts and culture of local wisdom with identical characteristics to Curuglemo Village. It was in this search for character, according to the results of discussions with the village head and Bumdes chair, that several program design solutions were needed by the village. Namely, training in batik with the typical Curuglemo motif where this motif is the result of research from artifact ornamentation found in Curuglemo and then combined with the character of agricultural fields and beautiful natural scenery with very distinctive natural textures and mountains which are the basis for the typical batik motifs of Curuglemo village. This batik training will empower women and young people in the village, so that young people can work in their own villages without having to migrate to cities as has been the case so far. Apart from batik training, digital marketing training will also be held through You Tube, Tiktok, Instagram and Website content. Digital marketing and websites are made using the Design Thinking and Human Centered Design (HCD) methods so that the design runs systematically. This training is based on visual communication design, namely persuasion, identity and information that are integrated in design media and published on digital platforms to increase tourism and sales of agricultural products, fields, traditional food products, handicrafts. So that it can be an income for young people by creating content designs on these digital platforms. This of course can make the target consumers of 2 Curuglemo village even wider. It is hoped that the creation of websites, digital marketing and typical village batik motifs can promote entrepreneurship in the local area.